Effect of clariflocculator and pulsator based sedimentation technology and poly-aluminium chloride coagulant type on the efficiency of the water treatment plant. Issue 3 (14th December 2021) - Maldhure, Atul; Khadse, Gajanan; Labhasetwar, Pawan
Abstract: Polyaluminium chloride (PAC) with different basicity is used as a coagulant in most drinking water treatment plants (WTP). The aluminium concentration in PAC and its hydrolysis mechanism varied with the basicity of PAC. Incremental addition of PAC changes various physico-chemical properties and turbidity removal mechanisms in water. Water treatment plants use the PAC concentration beyond its optimum dose without considering other aspects, including residual aluminium concentration. In the present work, the effect of high and medium basicity of PAC on different physico-chemical properties like pH, zeta potential, and residual aluminium concentration of water was investigated. The pH of treated water decreases with the incremental addition of PAC, and an increase in zeta potential and residual aluminium concentration in treated water was evidenced. The change in pH after PAC addition is responsible for deciding the coagulation mechanism and efficiency of the coagulation process. pH reduction is comparatively more in high basicity PAC than medium basicity. PAC hydrolysis mechanism is controlled by the zeta potential of water and can be used as an alternative method to decide the optimum coagulant dose. The performance of clariflocculator and pulsator-based WTP was also evaluated for raw water from the same source. To reduce down the turbidity below the acceptable level, the coagulant requirement for clariflocculator based WTP is comparatively less than pulsator based WTP. The floc blanket in the pulsator gets disturbed with a slight change in the coagulant chemistry and quantity. HIGHLIGHTS: Performance of clariflocculator and pulsator-based WTP was studied for the same raw water source. Clariflocculator based WTP required comparatively less coagulant than pulsator based WTP to remove turbidity below 1 NTU. Incremental coagulant addition decreases pH and enhances zeta potential and residual Al in treated water. Floc blanket in the pulsator gets disturbed with a small change in the coagulant chemistry and quantity.